Comparing disease activity indices in ulcerative colitis. (1st April 2014) - Walsh, A.J.; Ghosh, A.; Brain, A.O.; Buchel, O.; Burger, D.; Thomas, S.; White, L.; Collins, G.S.; Keshav, S.; Travis, S.P.L.
Abstract: Background: Comparisons between disease activity indices for ulcerative colitis (UC) are few. This study evaluates three indices, to determine the potential impact of inter-observer variation on clinical trial recruitment or outcome as well as their clinical relevance. Methods: One hundred patients with UC were prospectively evaluated, each by four specialists, followed by videosigmoidoscopy, which was later scored by each specialist. The Simple Clinical Colitis Activity (SCCAI), Mayo Clinic and Seo indices were compared by assigning a disease activity category from published thresholds for remission, mild, moderate and severe activity. Inter-observer variation was evaluated using Kappa statistics and its effect for each patient on recruitment and outcome measures for representative clinical trials calculated. Clinical relevance was assessed by comparing an independently assigned clinical category, taking all information into account as if in clinic, with the disease activity assigned by the indices. Results: Inter-observer agreement for SCCAI (κ = 0.75, 95% CI 0.70–0.81), Mayo Clinic (κ = 0.72, 95% CI 0.67–0.78) and Seo (κ = 0.89, 95% CI 0.83–0.95) indices was good or very good as was the agreement for rectal bleeding (κ = 0.77) and stool frequency (κ = 0.90). Endoscopy in the Mayo Clinic index had the greatest variation (κ = 0.38). Inter-observer variation alone would have excluded up to 1 in 5 patients from recruitment or remission criteria in representative trials. Categorisation by the SCCAI, Mayo Clinic and Seo indices agreed with the independently assigned clinical category in 61%, 67% and 47% of cases respectively. Conclusions: Trial recruitment and outcome measures are affected by inter-observer variation in UC activity indices, and endoscopic scoring was the component most susceptible to variation.